Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1007/11866763_54
|View full text |Cite
|
Sign up to set email alerts
|

CFD Analysis Incorporating the Influence of Wall Motion: Application to Intracranial Aneurysms

Abstract: Abstract. Haemodynamics, and in particular wall shear stress, is thought to play a critical role in the progression and rupture of intracranial aneurysms. A novel method is presented that combines image-based wall motion estimation obtained through non-rigid registration with computational fluid dynamics (CFD) simulations in order to provide realistic intra-aneurysmal flow patterns and understand the effects of deforming walls on the haemodynamic patterns. In contrast to previous approaches, which assume rigid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
62
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 11 publications
4
62
0
3
Order By: Relevance
“…CFD is traditionally performed by using generalized inflow boundary conditions based on typical flow rates in a healthy adult. [14][15][16][17][18][19][20][21][22][23][24][25][26][27] Recently, several studies have replaced these generalized inflow boundary conditions by patient-specific velocity measurements in the vessels proximal to the aneurysm. 10,12,[28][29][30][31][32] In these studies, either 2D phase-contrast MR imaging (PC-MR imaging) or transcranial Doppler sonography was used to measure the flow.…”
mentioning
confidence: 99%
“…CFD is traditionally performed by using generalized inflow boundary conditions based on typical flow rates in a healthy adult. [14][15][16][17][18][19][20][21][22][23][24][25][26][27] Recently, several studies have replaced these generalized inflow boundary conditions by patient-specific velocity measurements in the vessels proximal to the aneurysm. 10,12,[28][29][30][31][32] In these studies, either 2D phase-contrast MR imaging (PC-MR imaging) or transcranial Doppler sonography was used to measure the flow.…”
mentioning
confidence: 99%
“…However, these assumptions are believed to have relatively limited influence on the predicted flow patterns. 28 The influence of mesh resolution is reported in an article by Valen-Sendstad and Steinman, 29 in which they have shown that lower resolution meshes can result in different oscillatory shear index values as opposed to higher resolution models. Not using the very-high-resolution models may have disguised the associations between oscillatory shear index and rupture status; however, this issue was beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the use of idealized, rigid models facilitated fundamental understanding of the effects that two different design geometries had on flow. Based on previous literature, the global flow and stress profiles generated by compliant wall simulations are similar to those from the rigid simulation case (Zhao et al 2000;Dempere-Marco et al 2006). Accordingly, rather than using our computational resources to accomplish a handful of compliant model simulations, we chose to explore a more extensive range of boundary conditions, which (such as geometry) generally have greater impact on fluid dynamic outcomes (Cebral et al 2011).…”
Section: Discussionmentioning
confidence: 99%